Study of the Efficacy of Real Time-PCR Method for Amikacin Determination Using Microbial Assay - Farzaneh Lotfipour; Farshid Yeganeh; Elnaz Tamizi; Amin Zahedi; Mohammadreza Asefi (Tabriz University of Medical Sciences, 2015)
Purpose: Microbial assay is used to determine the potency of antibiotics and vitamins. In spite of its advantages like simplicity and easiness, and to reveal the slight changes in the molecules, the microbial assay suffers from significant limitations; these methods are of lower specificity, accuracy and sensitivity. The objective of the present study is to evaluate the efficacy of real time-PCR technique in comparison with turbidimetric method for microbial assay of amikacin. Methods: Microbial determination of amikacin by turbidimetric method was performed according to USP. Also amikacin concentrations were determined by microbial assay using taq-man quantitative PCR method. Standard curves in different concentration for both methods were plotted and method validation parameters of linearity, precision and accuracy were calculated using statistical procedures. Results: The RT-PCR method was linear in the wider concentration range (5.12 - 38.08 for RT-PCR versus 8.00 - 30.47 for turbidimetric method) with a better correlation coefficient (0.976 for RT-PCR versus 0.958 for turbidimetric method). RT-PCR method with LOQ of 5.12 ng/ml was more sensitive than turbidimetric method with LOQ of 8.00 ng/ml and the former could detect and quantify low concentrations of amikacin. The results of accuracy and precision evaluation showed that the RT-PCR method was accurate and precise in all of the tested concentration. Conclusion: The RT-PCR method described here provided an accurate and precise technique for measurement of amikacin potency and it can be a candidate for microbial determination of the antibiotics with the same test organism.